An observation of selected national bodies relating to the religion of Islam in the federation of Malaysia - Mokhtar, Khairil Azmin (2006)
The paper focuses on a few national bodies that has been specifically founded to achieve the objectives, and the bodies that have these objectives apart from having other roles and functions. The aim of this national bodies and the authority they have to achieve the objectives are observed and analyzed. The effect of the role and power of these bodies to the division of power between federal government and state government over religious matters are also analyzed to a certain extent.